2015
DOI: 10.1016/j.jhealeco.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Recessions, healthy no more?

Abstract: Over the 1976-2010 period, total mortality shifted from strongly procyclical to being weakly or unrelated to macroeconomic conditions. The association is likely to be poorly measured when using short (less than 15 year) analysis periods. Deaths from cardiovascular disease and transport accidents continue to be procyclical; however, countercyclical patterns have emerged for fatalities from cancer mortality and external causes. Among the latter, non-transport accidents, particularly accidental poisonings, play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
171
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(195 citation statements)
references
References 57 publications
16
171
1
7
Order By: Relevance
“…Specifically, in the E.U., rising unemployment rates during the Recession were associated with declining mortality among individuals <65 years [36], while studies that looked at mortality among all age groups combined reported no effect [37,41]. In the U.S., the previously described association between rising unemployment and declining mortality appears to have tapered off before the onset of the Recession [39]. Individual and multilevel analyses also found that older individuals in the U.S. who lost their jobs during recessions faced increasing mortality risk [40].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, in the E.U., rising unemployment rates during the Recession were associated with declining mortality among individuals <65 years [36], while studies that looked at mortality among all age groups combined reported no effect [37,41]. In the U.S., the previously described association between rising unemployment and declining mortality appears to have tapered off before the onset of the Recession [39]. Individual and multilevel analyses also found that older individuals in the U.S. who lost their jobs during recessions faced increasing mortality risk [40].…”
Section: Resultsmentioning
confidence: 99%
“…He speculates that rising opportunity costs may be an explanation. Using more recent data, from 1976 through 2009, Ruhm (2015) points to a shift over time in the relationship between total mortality and economic conditions; from being procyclical to being unrelated. This shift is however not the same across causes of mortality.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Examined possible mechanisms for the procyclicality of overall mortality in the United States have mostly been personal income (Ruhm 2000), health behaviours (Ruhm 2003(Ruhm , 2007(Ruhm , 2015, and individual labour market status (Miller et al 2009). Miller et al (2009) find that the added deaths related to a rise in the unemployment rate are mostly for age groups that are not likely to be a part of the labour force; only 7% of additional deaths were for the age group 25-64.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations